Does masting result in frugivore satiation? A test with Manilkara trees in French Guiana - Mendoza, Irene [UNESP]; Martin, Gabrielle; Caubère, Adeline; Châtelet, Patrick; Hardy, Isabelle; Jouard, Sylvie; Forget, Pierre-Michel (Cambridge University Press (CUP), 2015)
Species showing mast seeding synchronously produce large amounts of fruits during some scattered years. This massive crop has been hypothesized to improve dispersal effectiveness by a satiation of seed predators, but the consequences for seed dispersers have barely been studied in the tropics. We tested the hypothesis that masting resulted in satiation of frugivorous dispersers using the study case of two Manilkara species growing in an Amazonian forest in French Guiana. Seed dispersal was estimated by means of seed traps in two forest types during a 10-y monitoring. Manilkara huberi and M. bidentata showed three fruiting events in a time span of 10 y (in 2001, 2006 and 2010). Estimates of seed dispersal from 2001 and 2010 showed that satiation of frugivores only occurred in the year with the largest crop of Manilkara (2010) and in the habitat where the diversity of primate-dispersed species retrieved in seed traps was the highest (Grand Plateau, with clay soils), while fruit consumers did not seem to be satiated in other instances. Spatio-temporal variability of seed production and the community-crop context are therefore affecting satiation of frugivores during masting events.
Keywords: frugivory; Manilkara bidentata; Manilkara huberi; mass fruiting; predator satiation hypothesis; primates; seed dispersal; spatio-temporal variation